Rancang Bangun Sistem E-Commerce Umkm Bobapeer Menggunakan Python Dengan Framework Flask - Fathon, Ulil; Diana Laily Fithri (Computer Science and Information Technology, 2024)
Along with the development of the internet in this increasingly advanced digital era, it encourages the growth of technology as a solution to improve business performance. One of the developing technologies is website-based applications which are one of the strategic solutions to increase competitiveness, with website-based applications being able to help promote, market, and sell products more widely. This study develops a website-based e-commerce system for UMKM Bobapeer, a boba drink business, with the aim of supporting promotion, sales, and operational management more efficiently. The system is designed using the Waterfall method, this study goes through the stages of planning, needs analysis, system design, development, testing, and implementation. The Python Flask framework was chosen as the main tool in system development. The results of this system development provide an effective solution to increase product visibility, facilitate transactions, and increase customer satisfaction